Uji Kelalaian Medis: Sebuah Kajian Literatur - Yen, Liauw Djai; Renate, Anastasia Refina; Farrand, Evelyn Tena; Theresia, Fransisca; Stefani, Maria; Liem, Sherly; Thamrin, Verdy Dharmawan; Ali, Veronika Wijaya; Lunita, Vincentia Melly Putri (Indonesian Journal of Legal and Forensic Sciences (IJLFS); Vol 12 No 1 (2022): Indonesian Journal of Legal and Forensic SciencesDO - 10.24843/IJLFS.2022.v12.i01.p02, 2022)
Medical negligence is a constant issue in medical practice in which its occurrence is constantly increasing, putting patients’ safety at risk. In Indonesia, medical negligence dispute settlement is done by the methods of litigation and non-litigation. However, there is currently no explicit law regarding medical malpractice, medical negligence and medical risk in Indonesia, hence, cases of medical risk are often mistakenly regarded as malpractice. In essence, there are several tests used as benchmarks to regard cases as medical negligence; that includes the Bolam test, Bolitho test and Montgomery test. This literature review aims to present an overview of each test currently used for medical negligence dispute settlement, whereas its application could aid in solving medical disputes in Indonesia.